Family law. Vol. 1, Family laws and constitutional claims - Flavia (New Delhi ; Oxford : Oxford University Press, 2011)
This detailed study on family law in India attempts to combine women's rights into legal theory, and uses case laws extensively. It discusses the concepts of justice, law, and gender, examines various personal laws related to marriage, property rights, succession, and divorce, and considers the different constitutional provisions important to personal laws and the role of the judiciary in the reconciliation of personal laws of each community and the supreme constitutional provisions.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Domestic relations -- India; Women's rights -- India; Constitutional law -- India; Citizenship -- India